Reasons for language shift in Peninsular Malaysia - David, Maya Khemlani (Journal of Modern Languages, 2017)
Malaysia is a multi-ethnic, multi-lingual country with a population (1999) of about 22 million people and at least a hundred languages. There are three main ethnic groups in Malaysia i.e. Malays (61%), Chinese (28%), Indians (8%) (Khoo: 1991:40). Within each ethnic group, there are found a variety of languages and dialects. Malay is the medium of instruction in national schools, in contrast Chinese and Tamil are used as the medium of instruction in national type schools. However, at the secondary level, Malaysians can only attend national school where Malay is used as the medium of instruction. As for English, it is a compulsory second language in both types of schools. The Third Malaysian Plan 1976-80 states that "Bahasa Malaysia (Malay) is the basis for national integration" but the Plan also states quite emphatically that "measures will be taken to ensure that English is taught as a strong second language" (Government of Malaysia 1976:386). Given this background, we find that many communities in Peninsular Malaya are experiencing language shift (see for example David, 1996 on the Sindhis; David, Naji and Sheena, 2003 on the Punjabis in the Klang Valley; David and Naji 2000 on the Tamils, David and Noar, 2001 on the Portuguese in MaJacca; David and Nambiar 2003 on the Malayalee Christians; David, 2003 on the Pakistanis in Machang, Kelantan; Nambiar 2002 on the Malayalee Muslims; Mohamad Subakir Mohd Yasin, 2003 on the Javanese community, and Mukerjee, 2002 on the Bengali community). It is surprising that the same thing should be happening to so many groups at the same time when we consider that the languages themselves are so different from each other, the attitudes about the surrounding sociery are different, and their histories are so different. The language they are shifting to is different: some are shifting to the national language or a dialect of Malay while others are shifting to an international language, English. Why, with such diversity, are these languages in such a similar precarious situation? Finding an answer to this question is important for the speakers of indigenous languages in Malaysia and is important for anyone involved in languageÂ·related work in these communities.